Arabidopsis Response to Inhibitor of Cytokinin Degradation INCYDE: Modulations of Cytokinin Signaling and Plant Proteome - Berková, Veronika; Kameniarová, Michaela; Ondrisková, Vladěna; Berka, Miroslav; Menšíková, Simona; Kopecká, Romana; Luklová, Markéta; Novák, Jan; Spíchal, Lukáš; Rashotte, Aaron M; Brzobohatý, Břetislav; Černý, Martin (Plants (Basel, Switzerland), 2020)
Cytokinins are multifaceted plant hormones that play crucial roles in plant interactions with the environment. Modulations in cytokinin metabolism and signaling have been successfully used for elevating plant tolerance to biotic and abiotic stressors. Here, we analyzed Arabidopsis thaliana response to INhibitor of CYtokinin DEgradation (INCYDE), a potent inhibitor of cytokinin dehydrogenase. We found that at low nanomolar concentration, the effect of INCYCE on seedling growth and development was not significantly different from that of trans-Zeatin treatment. However, an alteration in the spatial distribution of cytokinin signaling was found at low micromolar concentrations, and proteomics analysis revealed a significant impact on the molecular level. An in-depth proteome analysis of an early (24 h) response and a dose-dependent response after 168 h highlighted the effects on primary and secondary metabolism, including alterations in ribosomal subunits, RNA metabolism, modulations of proteins associated with chromatin, and the flavonoid and phenylpropanoid biosynthetic pathway. The observed attenuation in stress-response mechanisms, including abscisic acid signaling and the metabolism of jasmonates, could explain previously reported positive effects of INCYDE under mild stress conditions.
Keywords: proteome; stress response attenuation; CKX; Arabidopsis thaliana; cytokinin; inhibitor of cytokinin degradation